1995
DOI: 10.1139/f95-779
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic microsatellite loci from Atlantic salmon (Salmo salar): genetic differentiation of North American and European populations

Abstract: Atlantic salmon populations show Bow levels of genetic differentiation relative to other salmonid species, when surveyed by allozymes, and with mitochondrial DNA and nuclear ribosomal DNA markers. Here we report the application of three novel microsatellite VNTR loci to population differentiation in Atlantic salmon. A total of 232 microsatellites, cloned from Atlantic salmon, were classified as perfect. imperfect, and compound repeats. Microsatellite length, as in other teleosts, was significantly larger than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
4
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(103 citation statements)
references
References 40 publications
5
93
4
1
Order By: Relevance
“…The higher rates of mutation (and therefore polymorphism) of DNA markers result in greater power for population differentiation (Rousset and Raymond 1995;Goudet et al 1996). Levels of genetic differentiation demonstrated here for golden anchovy were higher than those significant values seen in Pacific herring (F ST = 0.023), Atlantic herring (F ST = 0.035), and widespread anadromous fish like Atlantic salmon (F ST = 0.054; McConnell et al 1997), where there was no genetic differentiation observed among populations. The high F ST values of this study are similar to those reported in other fish species (Cook et al 2002;Liao et al 2006) that revealed high and significant levels of genetic structure.…”
Section: Resultscontrasting
confidence: 73%
“…The higher rates of mutation (and therefore polymorphism) of DNA markers result in greater power for population differentiation (Rousset and Raymond 1995;Goudet et al 1996). Levels of genetic differentiation demonstrated here for golden anchovy were higher than those significant values seen in Pacific herring (F ST = 0.023), Atlantic herring (F ST = 0.035), and widespread anadromous fish like Atlantic salmon (F ST = 0.054; McConnell et al 1997), where there was no genetic differentiation observed among populations. The high F ST values of this study are similar to those reported in other fish species (Cook et al 2002;Liao et al 2006) that revealed high and significant levels of genetic structure.…”
Section: Resultscontrasting
confidence: 73%
“…All captive bred (hatchery) fish samples used here as controls showed allele length within the range previously described for brown trout (119-162 bp) (2,7,8). Samples taken from free-living populations, however, apart from the alleles within this range, produced several unusual alleles, well above the upper limit for brown trout and closer to the allele sizes observed in Atlantic salmon (6,11,12,14). electrophoretic profiles of the amplified Ssa197 fragments from the studied specimens can be seen in figs.…”
Section: Resultssupporting
confidence: 74%
“…A total of 18 loci were amplified in 3 multiplex reactions (full genotyping conditions available from authors upon request): SSsp3016 (GenBank no. AY372820), SSsp2210, SSspG7, SSsp2201, SSsp1605, SSsp2216 (Paterson et al 2004), Ssa197, Ssa171, Ssa202 (O'Reilly et al 1996), SsaD157, SsaD486, SsaD144 (King et al 2005), Ssa289, Ssa14 (McConnell et al 1995), SsaF43 (Sánchez et al 1996), SsaOsl85 (Slettan et al 1995), MHC I and MHC II . PCR products were analysed on an ABI 3730 Genetic Analyser and sized by a 500LIZ TM size standard.…”
Section: Genotypingmentioning
confidence: 99%